Peran Perempuan Dalam Penerapan Biopori Limbah Dapur Berbasis Ekofeminisme Di Dukuh Pengkol Desa Planggu - Difa Gamar Azizah (CV. Multi Kreasi Media, 2026)
Pengkol, located within the administrative area of Planggu Village, Trucuk District, Klaten Regency, is a settlement where most residents depend on home-based doormat production, agriculture, and daily wage labor for their livelihoods. Consequently, residents tend to prioritize meeting their daily economic needs over managing the residential environment. This condition has contributed to the limited management of organic kitchen waste generated daily by households. This community service activity aimed to enhance community awareness, particularly among women, of the relationship between environmental conservation and gender equality through an ecofeminist perspective, while introducing Lubang Resapan Biopori (LRB) as a household-based solution for managing organic kitchen waste. The activity was conducted using a non-research approach through four methods: education, socialization, demonstration, and hands-on practice. The program began with a field assessment and coordination with village officials and Organisasi Pemuda Pemudi Pengkol (OPPEL), followed by the dissemination of ecofeminist concepts and a technical demonstration on constructing biopore infiltration holes. The activity concluded with the installation of three pilot biopore infiltration holes together with community members. The results indicated an improvement in participants' understanding of the relationship between gender and environmental issues, increased awareness of the important role of women in household waste management, and the development of residents' technical skills in independently constructing and maintaining biopore infiltration holes. Keywords: Biopore Infiltration Holes, Community Service, Ecofeminism, Kitchen Waste, Women's Roles.